Neurorestorative Role of Stem Cells in Alzheimer’s Disease: Astrocyte Involvement - S. Choi, Sung; Lee, Sang-Rae; J. Lee, Hong (Current Alzheimer Research, 2016)
Neurogenesis is maintained in both neonatal and adult brain, although it is dramatically reduced in aged neurogenic brain region such as the subgranular layer and subventricular zone of the dentate gyrus (DG). Astrocytes play important roles for survival and maintenance of neurons as well as maintenance of neurogenic niche in quiescent state. Aβ can induce astrocyte activation which give rise to produce reactive oxygen species (ROS) and cytotoxic cytokines and chemokines, and subsequently induce neuronal death. Unfortunately, the current therapeutic medicines have been limited to reduce the symptoms and delay the pathogenesis of Alzheimer’s disease (AD), but not to cure it. Stem cells enhance neurogenesis and Aβ clearing as well as improved cognitive impairment. Neurotrophins and growth factors which are produced from both stem cells and astrocytes also have neuroprotective effects via neurogenesis. Secreted factors from both astrocytes and neural stem cells also are influenced in neurogenesis and neuron survival in neurodegenerative diseases. Transplanted stem cells overexpressing neurogenic factors may be an effective and therapeutic tool to enhance neurogenesis for AD.
Keywords: transplantation